Transcriptome analysis of rare minnow (Gobiocypris rarus) infected by the grass carp reovirus. Issue 89 (June 2019) - Lin, Yusheng; Wang, Bing; Wang, Nenghan; Ouyang, Gang; Cao, Hong
Abstract: Grass carp shares the largest portion of the aquaculture production in China, but hemorrhagic disease caused by grass carp reovirus (GCRV) often results in tremendous loss of fingerlings and yearlings, causing significant economic damages. However, it is difficult to study antiviral mechanisms in grass carp in vivo due to its large size and long reproductive cycle. Therefore, a small cyprinid species named rare minnow with high sensitivity to GCRV, is regarded as a useful model to study the mechanisms of this disease. In this study, rare minnows were infected with the type-IIGCRV (GCRV-HZ08), and pathogenesis was investigated by BGISEQ-500 transcriptome sequencing of four cDNA libraries, hepatopancreas, gills, head-kidney and spleen, and real time quantitative PCR (qRT-PCR). We obtained 51.22 Gb bases in total, and de novo assembled 107, 756 unigenes with an average length of 1, 441 bp. GO analysis revealed that the differentially expressed genes (DEGs) involved in the defense mechanisms were the most enriched GO terms in all four tissues. KEGG analysis revealed that the most enriched pathways were "Influenza A", "Herpes simplex infection", "Transcriptional misregulation in cancer" and "Metabolic" pathways. We also performed a comparative transcriptomic study between GCRV-infected rare minnow and grass carp data. This revealed that "IL-17 signaling pathway", "NF-kappa B signaling pathway" and "Influenza A" pathways are conserved (important) in the regulation of anti-GCRV infection in both species, and need to be further investigated. Furthermore, a total of four immune-related DEGs were selected for qRT-PCR validation, and the results confirmed the RNA-seq data. These results enhance our understanding of the antiviral responses of cyprinid fish infected by GCRV. Highlights: We analyzed the transcriptome of rare minnow after viral challenge with type-II GCRV. Influenza A pathway plays a critical role in defense mechanism against GCRV in fish. Rare minnow is a suitable model to study the anti-GCRV immune responses in vivo .